Drought Tolerant Nature of Grewia Species and Acacia Species - Poonam Sharma; Kalpana Agarwal (Journal of Coastal Life Medicine, 2023)
Global warming is a big issue now these days all over the world. Plants not only prevent the climate from abiotic stress like drought but also used for other purposes. It is the need of the present scenario to find out the drought tolerant taxa. The impact of drought in Grewia tenax and Grewia asiatica has not been studied so far; therefore the present study was conducted with an objective of studying the effect of drought on both Grewia species, by estimation of leaf expansion; and pigment concentration. In the study, Acacia nilotica was taken as control. Relative % change in leaf length (39.97%) and leaf area (32.72%) was observed minimum in G. tenax whereas G. asiatica had the lowest relative change in chlorophyll a (35.17%) and total chlorophyll (50.46%) content. Results indicated the tolerance towards drought in Grewia species.